2008
DOI: 10.1590/s1516-635x2008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Hatching distribution and embryo mortality of eggs laid by broiler breeders of different ages

Abstract: This study investigated the hatching distribution of eggs from broiler breeders of different ages in distinct periods of incubation. Eggs were incubated in a single-stage experimental incubator. A number of 3.510 eggs were distributed into 3 treatments with 13 replicates of 90 eggs each. Treatments corresponded to breeder age: young (34 weeks), intermediate-age (44 weeks) and old (72 weeks) breeders. Eggs were transferred to the hatcher at 432 incubation hours, hatching was first checked at 449 hours, after wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
2
18
1
3
Order By: Relevance
“…Almeida et al (2008) observed that older hens laid more infertile eggs and had higher embryonic mortality, which could be the reason for increased dam PE variance. The heterogeneity of total variance across ages and observed changes of variance components with age indicate that the use of random regression methodology is essential for the analysis of repeated measures of hatchability as the flock ages.…”
Section: Discussionmentioning
confidence: 94%
“…Almeida et al (2008) observed that older hens laid more infertile eggs and had higher embryonic mortality, which could be the reason for increased dam PE variance. The heterogeneity of total variance across ages and observed changes of variance components with age indicate that the use of random regression methodology is essential for the analysis of repeated measures of hatchability as the flock ages.…”
Section: Discussionmentioning
confidence: 94%
“…This study allowed to describe the EM according to the ages of the breeder flocks, determining aspect in the evaluation of the EM and that has been widely discussed in multiple experimental studies (5,12,16). The EM was higher in eggs from the 64 weeks old breeders, followed by the 40, 28 and 47 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Este estudio permitió describir la ME de acuerdo con la edad de las reproductoras, aspecto que es determinante en la evaluación de la ME y ha sido ampliamente discutido en múltiples estudios experimentales (5,12,16). La ME fue más alta en los huevos de las reproductoras de 64 semanas, seguida de las de 40, 28 y 47 semanas.…”
Section: Discussionunclassified
“…Therefore, posthatch BW loss may not be exclusively the result of dehydration. Dehydration as a result of extended post-hatch holding has been associated with poor post-hatch performance (Joseph & Moran 2005;Almeida et al, 2008). It has been reported that chick BW at pull time was significantly influenced by time of emergence from the shell as chicks that hatched early lost BW while waiting to be pulled and subsequently weighed less than later hatching chicks at pull time (Reis et al, 1997;Sklan et al, 2000;Joseph & Moran, 2005;El Sabry et al, 2013).…”
Section: Effect Of Hatching Time On Yolk Sac Percentage and Broiler Lmentioning
confidence: 99%